Comparison of physical characteristics among english professional and semi-professional soccer players across different leagues - Ripley, N. J.; Fahey, J.; Jones, P.; Batsford, J.; Sindall, P.; Bramah, C.; Comfort, P. (PLOS ONE, 2025)
The purpose of the present study was to investigate if differences exist in neuromuscular qualities between different leagues in English male soccer. Twenty soccer players (age: 23.3 ± 5.2 years, stature: 180.3 ± 7.0 cm, mass: 82.5 ± 7.7 kg) from English football league two (EFL2). 34 soccer players (age: 25.8 ± 4.3 years, stature: 180.9 ± 5.6 cm, mass: 81.4 ± 8.6 kg) from National league (NL) and 23 soccer players (age: 27.5 ± 4.3 years, stature: 182.1 ± 5.5 cm, mass: 84.1 ± 8.0 kg) from National league North (NLN). Each player completed three to five repetitions of the countermovement jump (CMJ), countermovement rebound jump (CMJRJ) and isometric mid-thigh pull (IMTP). Trivial to small differences were observed in CMJ jump height, CMJ momentum, relative average braking and propulsion force, time to take-off and modified reactive strength index (RSI) (p > 0.265, d = 0.05-0.55). However, moderate to large (p = 0.009, d = 0.94-1.25) differences were observed in countermovement depth. Trivial to moderate differences were observed in absolute and relative peak net force and force at 100 and 250 ms (p = 0.092, d = 0.13-0.63). Trivial to moderate differences were observed in CMJRJ rebound jump height and rebound jump momentum (p = 0.440, d = 0.17-0.41). NLN players had longer rebound contact time and lower rebound RSI, rebound average relative braking and propulsion forces to a large magnitude (p = 0.001, d = 1.18-1.85), with small differences between ELF2 and NL (p > 0.536, d = 0.11-0.39). Lower reactive qualities of NLN players could explain observed leagues, considering their relationship with match scoring situations. All players would be considered weak (<30 N/kg) and practitioners should prioritise lower limb strength across all leagues.